2004
DOI: 10.1158/0008-5472.can-03-2328
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Complement Factor H by Lung Cancer Cells

Abstract: The complement system is important in immunosurveillance against tumors. However, malignant cells are usually resistant to complementmediated lysis. In this study, we examine the expression of factor H, an inhibitor of complement activation, and factor H-like protein 1 (FHL-1), its alternatively spliced form, in lung cancer. We also evaluate the potential effect of factor H/FHL-1 in the protection of lung cancer cells against the activation of the complement cascade. By Northern blot analysis we demonstrate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 52 publications
4
60
0
Order By: Relevance
“…CFH, a 140 kDa plasma glycoprotein with nine N-glycosylation sites, is a major regulator of the alternative complement pathway 39 that mediates the escape of malignant cells from complement-cytotoxicity. 4043 No information in this regard is available for HCC, and we are not aware of any study reporting glycosylation changes in CFH in the context of liver disease.…”
Section: Resultsmentioning
confidence: 99%
“…CFH, a 140 kDa plasma glycoprotein with nine N-glycosylation sites, is a major regulator of the alternative complement pathway 39 that mediates the escape of malignant cells from complement-cytotoxicity. 4043 No information in this regard is available for HCC, and we are not aware of any study reporting glycosylation changes in CFH in the context of liver disease.…”
Section: Resultsmentioning
confidence: 99%
“…The recent definition of complement factor H, which inhibits C3 deposition and C5a release after complement activation (31), and toll-like receptor-4, which influences C3 deposition and is negatively regulated by C5a (32,33), as major susceptibility loci in AMD (34)(35)(36)(37)(38)(39) adds to the mounting evidence of complement dysfunction in this disease. These findings and ours enrich the growing recognition that the complement system is not dedicated solely to immunological surveillance but also can play a versatile role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II clinical trial, pancreatic cancer was shown to inhibit the MBL pathway and treatment with ω-3–rich fatty acids and gemcitabine restored MBL activity, improving patient survival [43]. In contrast, lung cancer cells evade complement-mediated cell lysis by overexpressing the alternative pathway inhibitor FH [44]. Additional studies indicate that cancer cells utilize the classical pathway to their advantage.…”
Section: 0 the Role Of Complement Evasion In Diseasementioning
confidence: 99%